VIDEO-LAPAROSCOPIC INTERVENTIONS IN DIAGNOSTICS AND TREATMENT OF TORSION AND NECROSIS OF APPENDICES EPIPLOICA - M. E. Timofeev; E. D. Fedorov; A. P. Krechetova; S. G. Shapovalyants (Вестник хирургии имени И.И. Грекова)
A retrospective analysis of treatment of 82 patients with torsion and necrosis of appendices epiploica was made. The video-laparoscopic surgery of these patients was performed. When the diagnosis is unclear, the differential diagnostics should be made between the appendices epiploica disease and other abdominal diseases using the video-laparoscopy. This method allowed the establishment of the correct diagnosis of torsion and necrosis of appendices epiploica in 95,1% of patients. The laparoscopic treatment was made in 87,8% of cases with minimal quantity of postoperative complications. The video-laparoscopy allowed the detection of accompanying pathology of abdominal organs and performance of the correction by low-invasive method. The need of conversion occurred in 12,2% of patients. Postoperative period was characterized by uneventful recovery, minimal usage of analgesics and antibiotics, early stages of rehabilitation, perfect cosmetic effect in majority of patients.